Low‐cost wideband double‐layer microstrip coupled‐line directional coupler with high directivity. Issue 7 (July 2014) - Esfeh, Babak Kazemi; Raskin, Jean‐Pierre; Van, Wendy
ABSTRACT In this article, a low‐cost double‐layer microstrip structure with a gap space between the two substrate layers is used to develop a microstrip coupled‐line directional coupler with high directivity. The proposed design shows a high directivity (more than 20 dB) over a wide frequency bandwidth (more than 2 GHz). The double‐layer directional coupler, designed on FR4 substrate material at 2.4 GHz provides more than 30 dB isolation. The simulation and measurement results are in good agreement. By applying a simple and low‐cost fabrication process and design, the directivity of the directional coupler is enhanced by more than 10 dB compared with a microstrip structure. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1570–1575, 2014